Gridlock from diagnosis to treatment of multidrug-resistant tuberculosis in Tanzania: low accessibility of molecular diagnostic services and lack of healthcare worker empowerment in 28 districts of 5 high burden TB regions with mixed methods evaluation - Stellah G. Mpagama; Peter M. Mbelele; Anna M. Chongolo; Isaack A. Lekule; Johnson J. Lyimo; Gibson S. Kibiki; Scott K. Heysell (BMC, 2019)
Abstract Background Multidrug-resistant tuberculosis (MDR-TB) outcomes are adversely impacted by delay in diagnosis and treatment. Methods Mixed qualitative and quantitative approaches were utilized to identify healthcare system related barriers to implementation of molecular diagnostics for MDR-TB. Randomly sampled districts from the 5 highest TB burden regions were enrolled during the 4th quarter of 2016. District TB & Leprosy Coordinators (DTLCs), and District AIDS Coordinators (DACs) were interviewed, along with staff from all laboratories within the selected districts where molecular diagnostics tests for MDR-TB were performed. Furthermore, the 2015 registers were audited for all drug-susceptible but retreatment TB cases and TB collaborative practices in HIV clinics, as these patients were in principal targeted for drug susceptibility testing by rapid molecular diagnostics. Results Twenty-eight TB districts from the 5 regions had 399 patients reviewed for retreatment with a drug-susceptible regimen. Only 160 (40%) had specimens collected for drug-susceptibility testing, and of those specimens only 120 (75%) had results communicated back to the clinic. MDR-TB was diagnosed in 16 (13.3%) of the 120 specimens but only 12 total patients were ultimately referred for treatment. Furthermore, among the HIV/AIDS clinics served in 2015, the median number of clients with TB diagnosis was 92 cases [IQR 32-157] yet only 2 people living with HIV were diagnosed with MDR-TB throughout the surveyed districts. Furthermore, the districts generated 53 front-line healthcare workers for interviews. DTLCs with intermediate or no knowledge on the clinical application of XpertMTB/RIF were 3 (11%), and 10 (39%), and DACs with intermediate or no knowledge were 0 (0%) and 2 (8%) respectively (p = 0.02). Additionally, 11 (100%) of the laboratories surveyed had only the 4-module XpertMTB/RIF equipment. The median time that XpertMTB/RIF was not functional in the 12 months prior to the investigation was 2 months (IQR 1-4). Conclusions Underutilization of molecular diagnostics in high-risk groups was a function of a lack of front-line healthcare workforce empowerment and training, and a lack of equipment access, which likely contributed to the observed delay in MDR-TB diagnosis in Tanzania.